2018
DOI: 10.1521/jscp.2018.37.5.356
|View full text |Cite
|
Sign up to set email alerts
|

It's Not Me, It's You: Self- and Partner-Schemas, Depressive Symptoms, and Relationship Quality

Abstract: Depression is associated with a host of interpersonal difficulties, particularly within intimate relationships. Although a significant body of literature has supported the presence of a highly consolidated negative self-representation or selfschema, no studies have examined whether depression is also associated with a highly organized negative "partner-schema", and whether this represents a risk factor for relationship distress. Given the high degree of similarity between cognitive representations of self and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…In this sense, Wilde and Dozois (2018) found associations between partner schema and relationship satisfaction. Partner schemas containing concepts which are highly associated with a negative valence and poorly associated with a positive valence negatively explained part of the variance of relationship satisfaction.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this sense, Wilde and Dozois (2018) found associations between partner schema and relationship satisfaction. Partner schemas containing concepts which are highly associated with a negative valence and poorly associated with a positive valence negatively explained part of the variance of relationship satisfaction.…”
Section: Introductionmentioning
confidence: 84%
“…Despite the importance of social schemas in an individual's romantic life, studies that investigate actual romantic relationship and partner schemas are relatively rare. Furthermore, the instruments employed in studies to measure such schemas use previously defined concepts (e.g., Jose et al 2010;Rowley 1995;Whisman and Delinsky 2002;Wilde and Dozois 2018). Although it presents advantages, this method conditions the set of concepts of the researched schemas to the screening of the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of interpersonal schemas, a recent line of my research has focused on how the content and structure of these interpersonal schemas impact stress generation and interpersonal behaviors in depression (Dobson, Quigley, & Dozois, 2014; Dozois & Rnic, 2015; Evraire & Dozois, 2011, 2014; Wilde & Dozois, 2018, 2019; Wilde et al, in press). For example, several studies have demonstrated that core beliefs related to abandonment (and anxious attachment) are associated with excessive reassurance seeking (ERS; e.g., Evraire et al, 2011, 2014; Evraire, Ludmer, & Dozois, 2014).…”
Section: The Impact Of Self-schemas On Interpersonal Functioningmentioning
confidence: 99%
“…These ongoing maladaptive interactions and cognitive processes (e.g., activation of schemas and attributions) contribute to depression and relationship dissatisfaction and further reinforce and consolidate highly organized, negative self- and partner-schema structures. For instance, Wilde and Dozois (2018) found that partner-schemas predicted relationship quality and one’s attributions about the relationship over and above self-schemas (whereas self-schemas predicted depression more than did partner-schemas). Although some empirical support exists for this model, we are just beginning to test its various components and predictions, and further validation research is needed.…”
Section: Partner Schemasmentioning
confidence: 99%
“…The discrepancies may be due to the other-words used in these studies, which were words that did not refer to a specific object, such as “not me,” “he,” “she,” “others,” etc. Nevertheless, it is worth noting that the other-schema that plays a key role in MDD is the representation of those with whom the individual has intimate relationships, such as parents and partners ( 29 31 ). Similar to the present study, the other-words used in Yao et al’s ( 16 ) study were words such as parents and lovers, and they also found that the other-schema in MDD was more negative than that in HCs.…”
Section: Discussionmentioning
confidence: 99%